Profitability Moderates the Effect of Sustainability Report Disclosure, Dividend Policy, and Capital Structure on Firm Value in Sensitive Industries - Ni Komang Ayu Ariasih; Ayu Aryista Dewi (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
The high stock prices of sensitive industry companies despite having high environmental risks indicate that financial and non-financial factors play a crucial role in shaping firm value. This study aims to examine the effect of sustainability report disclosure, dividend policy, and capital structure on firm value with profitability as a moderating variable. The research sample consists of 29 sensitive industry companies listed on the Indonesia Stock Exchange for the 2021-2023 period, deterined through purposive sampling. The analysis was carried out using Moderated Regression Analysis (MRA) with SPSS. The results show that sustainability report disclosure and capital structure has a significant effect on firm value and profitability is not able to strengthen the three relationships. The findings emphasize that sensitive industries, inadequate sustainability report disclosure and capital structure can give negatif perceptions by investors toward firm value.